Principles of Medical Education - Singh, D. Daljit (Jaypee Brothers Medical Publishers, 2021)
The aim of this book is to focus on the principles of medical education. Medical education in India is in the throes of fundamental change; from the promise of new regulation to the definition of a new curriculum with a new structure, new ideas about how students should enter medical school, new ideas about how they should learn, new areas of content and new assessment-based methods of progression. This book consists of 31 chapters, which include teaching and learning, systems approach to instruction, group dynamics, curriculum, integrated teaching, domains of learning, writing instructional objectives, taking a lecture, tutorials and small group discussion, teaching clinical skills, one-minute preceptor, media in medical education, student assessment, essay question, innovative teaching-learning method, microteaching, teacher evaluation, reflective writing, and faculty development. This book is a useful training manual and also the resource for basic and advanced medical education workshops.